Identification of Potential Inhibitors From Urginea indica Metabolites Against Xanthomonas oryzae pv. oryzae and Magnaporthe oryzae Receptors - Mansoori, Aadil; Dwivedi, Anurag; Sharma, Kapil; Dubey, Sharad Kumar; Thakur, Tarun K.; Kumar, Anirudh (Frontiers in Agronomy, 2022)
Synthetic pesticides are extensively used in agriculture to control pests and prevent yield loss. However, excessive use imposes serious threat to human health, environment and biodiversity and hence, certain pesticides have been abandoned from agriculture applications. Thus, there is need to discover potential and ecofriendly pesticides for effective management of phytopathogens. In current study, Urginia indica bulb extract was evaluated for potential antimicrobials and antioxidant phytochemicals. The methanol and aqueous extract were prepared from the bulbs of Urginia indica and were evaluated for polyphenol contents, alkaloid, total antioxidant capacity, and iron chelating activity. Aqueous extract exhibited high phenol and flavonoid content, whereas total antioxidant activity was higher in methanol extract. The iron chelating activity of both methanolic and aqueous extract were approximately similar. The antioxidant activity of methanolic extract was presented by IC50 value which was 648±27.65 for DPPH, 403.55 ± 7.91 for ABTS and 324.44 ± 16.31 µg/ml for nitric oxide radicals scavenging activity. Likewise, the IC50 of aqueous extract was 789.52 ± 86.64 for DPPH, 722.58 ± 15.08 for ABTS and 275.58 ± 11.15 µg/ml for NO radicals scavenging activity. The functional group such as -OH, C-H, O=C=O, C=O, C=C, C-OH and CN were identified through fourier-transform infrared spectroscopy (FTIR) which indicate the presence of various compounds in the extract. Additionally, 75 metabolites were recorded through GC-MS, of which 23 were predicted to have antimicrobial activities. Consequently, metabolites were docked with D-alanine-D-alanine ligase A (DdlA) and Mitogen-activated protein kinase (MAPK1) of Xanthomonas oryzae pv. oryzae (Xoo) and Magnaporthe oryzae respectively to understand the possible mechanism of interaction between active metabolites and pathogen receptors (DdlA and MAPK1). Docking study revealed that Quinic acid 3 caffeoyl has highest binding affinity with both DdlA and MAPK1 with respect to reference compound D-cycloserine and Trametinib. Thus, Quinic acid 3 caffeoyl could inhibit both DdlA and MAPK1 mediated signal transduction and hence, could be used as a promising natural inhibitor of DdlA and MAPK1 receptors. Above results indicates that Urginia indica could be a potential source of bioactive compounds and could be used as a potential source of natural pesticide to suppress phytopathogens.